POLA PENGEMBANGAN PARAGRAF PADA TEKS BACAAN DALAM BUKU PELAJARAN BAHASA INDONESIA - Citra Winda Ulvia; Mulyanto Widodo; Munaris Munaris (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2015)
This research aimed to describe the pattern of paragraph development in reading text of Indonesian textbooks class VII SMP / MTs publication of Kemendikbud. The method that used in this research was qualitative descriptive method. The results showed that the pattern of paragraph development in reading text of Indonesian textbooks consisted of eleven patterns of paragraph development, they were: the comparison pattern paragraph development, the question pattern paragraph development , the cause and the effect pattern paraghraph development, the instance pattern paragraph development, the repetition pattern paragraph development, the definition pattern paragraph development, the detail pattern paragraph development, the illustration pattern paragraph development, the chronology pattern paragraph development,the division-classification pattern paragraph development, and the analogy pattern paragraph development.Penelitian ini bertujuan untuk mendeskripsikan pola pengembangan paragraf pada teks bacaan dalam buku pelajaran Bahasa Indonesia kelas VII SMP/MTs terbitan Kemendikbud. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Hasil penelitian ini menunjukkan bahwa pola pengembangan paragraf pada teks bacaan dalam buku pelajaran Bahasa Indonesia terdiri atas sebelas pola pengembangan paragraf yaitu pola pengembangan paragraf perbandingan, pola pengembangan paragraf pertanyaan, pola pengembangan paragraf sebab akibat, pola pengembangan paragraf contoh, pola pengembangan paragraf perulangan, pola pengembangan paragraf definisi, pola pengembangan paragraf pemerincian, pola pengembangan paragraf ilustrasi, pola pengembangan paragraf kronologi, pola pengembangan paragraf klasifikasi-divisi, dan pola pengembangan paragraf analogi.Kata kunci: paragraf, pola, teks bacaan.